2014
DOI: 10.2174/1566524014666140724103147
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cytoskeleton Protein and Extracellular Matrix Protein Induced by Stromal-Derived Nitric Oxide Promotes Lung Cancer Invasion and Metastasis

Abstract: Lung cancer commonly metastasizes to lymph nodes, brain and bones, which is the main cause of death. It is still a challenge to detect molecular biomarkers for early diagnosis and therapeutics of lung cancer. Our previous study found that bone marrow-derived stroma cells (BMSCs) under tumor microenvironment produced nitric oxide (NO), which was induced by inducible nitric oxide synthase (iNOS), and promoted invasion and metastasis of cancer cells by remodeling cytoskeleton. The aim of this study is to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Many factors are well known to be related to the metastatic or invasive potential of human cancer cells. For examples, nitric oxide promotes the invasive activity in lung cancer cells [36]; and changes energy metabolism (increased glycolysis), which affects the tumor-endothelial interaction of bladder carcinoma [37]. Recent evidence has suggested that calmodulin plays a crucial role in the modulation of cancer metastasis during gastric cancer [38].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors are well known to be related to the metastatic or invasive potential of human cancer cells. For examples, nitric oxide promotes the invasive activity in lung cancer cells [36]; and changes energy metabolism (increased glycolysis), which affects the tumor-endothelial interaction of bladder carcinoma [37]. Recent evidence has suggested that calmodulin plays a crucial role in the modulation of cancer metastasis during gastric cancer [38].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS derived NO have been associated with many tumors and in their progression into metastatsis. iNOS positivity has been reported consistently in human cancers at a variety of sites, including the lung [101] prostate [102] , breast [103] , bladder [104] , oral cavity, esophagus [105] and colon [106] . In each single case, the effects of NO have to be interpreted with regard to the microenvironment of the tumor.…”
Section: Tumor Inos and Nomentioning
confidence: 99%
“…iNOS may also serve as a biomarker for metastasis of lung cancer. In lung cancer patients with bone metastasis, the circulating metastatic cells were found to have increased iNOS expression contributing to increase in Epithelial Cell Adhesion Molecule (EpCAM) which is associated with metastasis due to reduced cell-cell-adhesion [101] .…”
Section: Tumor Inos and Nomentioning
confidence: 99%
“…nNOS and eNOS are constitutively present in peripheral nerves and vascular endothelial cells, respectively, whereas iNOS is inducible, mainly in pathological conditions, by mesenchymal cells and parenchymal cells through the stimulation of endotoxins and cytokines. The expression of NOS has been detected in various cancers such as breast, bladder, stomach, prostate, lung, colon, pancreas and renal cancers . In liver cancer, the expression pattern of NOS remains unknown.…”
Section: Introductionmentioning
confidence: 99%